A Simple Test of the Efficiency Wage Hypothesis Revisited - Parsis Dastani; François Laisney; Sophie Vouillaume (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1997)
Gerlach and Stephan (1994) proposed a test based on the idea that the wage premium, the part of the wage which is not explained by the stock of human capital, should help predict variables such as career expectations (quit, change occupation, leave the labour force) and some job characteristics (like degree of supervision). We examine a number of issues related to sample selection and split, as well as the choice of tenure and experience variables, and obtain surprisingly robust results, which differ somewhat from theirs: in particular, we find no effect of the wage premium on career expectations. The main source of these differences appears to lie in the pooling of Germans and foreigners.
Keywords: E24; J41; 330; Efficiency wages; wage equations